Dedication to David Dean - Joseph M. Ashley; John V. Pepper; Kirsten L. Rowe; Robert M. Schmidt; Steven Stern (IZA Journal of Labor Policy, 2014)
This special volume is dedicated to David H. Dean who passed away on August 11th, 2013. This dedication describes David's impact on the academic research on disability and, most notably, the vital interaction between research and policy. It discusses his influence in shaping perspectives on evaluating the effectiveness of programs to increase employment. Finally, it describes David as a person and why he was influential as a researcher and college professor.
Keywords: H51; I13; J24; 330; Vocational rehabilitation; Disability insurance; David Dean